Effects of the sampling time on the vaginal microbiota in healthy pregnant women: a prospective observational studyAJOG Global Reports at a Glance - Hiroshi Mori, MD; Eiji Shibata, PhD; Emi Kondo, MD; Mitsumasa Saito, PhD; Kiyoshi Yoshino, PhD; Kazumasa Fukuda, PhD (AJOG Global Reports)
Background: Studies using 16S rRNA gene sequencing have extensively examined the vaginal microbiota changes of pregnant women. However, no study has examined these changes considering the time of day at which vaginal fluid samples were collected from near-term pregnant women. Objective: To describe the vaginal microbiota of Japanese near-term pregnant women with normal pregnancy outcomes and potential vaginal microbiota changes from wake-up to bedtime. Study design: In this prospective observational study, vaginal swab specimens were obtained from healthy near-term pregnant women twice on the same day, after waking up and before bedtime. All specimens were examined for total bacterial cell count per gram of vaginal fluid, Nugent score, pH, and vaginal microbiota analysis using 16S rRNA gene sequencing. Initially, the wake-up and bedtime samples of all participants were analyzed at the genus level using next-generation sequencing. Subsequently, all samples were analyzed at the genus and species levels using Sanger sequencing. Results: Sixteen pregnant women were enrolled in this study. The median age of the participants was 32.5 years, and the median gestational age was 38 weeks. Median bacterial counts in vaginal fluids at wake-up and bedtime were 3.9 × 109/g and 3.6 × 109/g, respectively, with no significant difference. Vaginal microbiota analyses based on 16S rRNA genes showed that the vaginal microbiota in pregnant women with no abnormalities during pregnancy was limited to a single flora dominated by Lactobacillus spp. and included pregnant women with highly diverse vaginal microbiota. Genus-level analysis using next-generation sequencing showed that the vaginal microbiota differed between wake-up and bedtime in more diverse samples but not in less diverse samples. However, these differences were small compared to individual differences. The dominant genera in each sample had similar relative abundances in both wake-up and bedtime samples. However, the non-dominant genus Streptococcus spp. was significantly more frequently detected in bedtime samples. In species-level analyses, the proportions of dominant and non-dominant species showed little change between wake-up and bedtime. Conclusions: The vaginal microbiota of pregnant women with normal pregnancy outcomes was not necessarily dominated by Lactobacillus spp. Further studies are required to define the vaginal microbiota in healthy pregnant women. When vaginal fluid samples were collected from the same pregnant women at wake-up and bedtime under the same conditions, the differences between wake-up and bedtime samples were greater for women with high diversity of the vaginal microbiota than for those with low diversity. However, these differences were not sufficiently large to exceed individual differences, and almost no change in the abundances of the dominant genera was observed. Since the relative abundance of Streptococcus spp., a non-dominant species of the vaginal microbiota tends to change between wake-up and bedtime, it might be necessary to collect samples before bedtime to detect group B Streptococci.